Fundamentals of territorial issues in post-soviet central Central Asia: critical analysis (International relations and international law Journal, 2021)
In 2021, on the 30th anniversary of the collapse of the USSR as a political institution, a large-scale study has been publishing on the role of the soviet system in modern period. In the case of Central Asia, there are also a number of large-scale regional and interstate problems which were “inherited” from the Soviet regime and being a basis dispute for the last three decades. One of them is the unresolved territorial issues between the post-Soviet states of Central Asia. Currently, the main problem in Central Asia is the lack of demarcation of state borders between countries, in addition to transboundary rivers and electricity transmission. In particular, the Fergana Valley problem is a source of disagreement between Kyrgyzstan, Uzbekistan and Tajikistan. In the region, the Republic of Kazakhstan and Turkmenistan are the main countries with fully delimited state borders. However, the unresolved issue of the Fergana Valley in Central Asia poses a direct geopolitical threat not only to Tajikistan, Kyrgyzstan and Uzbekistan, but to the region as a whole. The emergence and formation of intraregional border disputes in Central Asia in the 1920s and 1930s, the Soviet system of government did not take into account the political and ethnic characteristics of the region, but only in terms of transport and logistics. imperial political interests. The article analyzes the territorial problems of Central Asia in the XXI century on the basis of the critical theory of social constructivism.Key words: Central Asia, Fergana Valley, territorial disputes, USSR, delimitation and demarcation, theory of constructivism.